Strategi Guru Mata Pelajaran Fiqh Dalam Peningkatkan Pemahaman Agama - Kamali, Ahmad Nur; Sugiyanto, Sugiyanto (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2024)
This study examines the strategies employed by fiqh teachers to enhance students' religious understanding at MA Raden Rahmat Mojowarno Jombang. Using a descriptive qualitative approach, the research reveals comprehensive efforts made by fiqh teachers through a combination of classroom learning and extracurricular religious activities. The main strategies include planning and implementing routine religious activities such as congregational Dhuha prayer, Qur'an recitation, and other religious practices. In the classroom, teachers apply varied learning methods including expository, heuristic, and reflective approaches. Despite facing challenges such as time constraints and limited infrastructure, teachers demonstrate creativity in optimizing available resources. The holistic approach implemented encompasses cognitive, affective, and psychomotor aspects, aiming not only to enhance theoretical understanding but also to shape students' character and behavior in accordance with religious values. This study highlights the importance of collaboration among schools, families, and communities in supporting students' religious education. The research findings indicate that the applied strategies have the potential to address the challenges of religious education in the modern era, yet require continuous evaluation and systemic support for long-term effectiveness.